Imaging of CD47 Expression in Xenograft and Allograft Tumor Models - Alexander Zheleznyak; Oluwatayo F. Ikotun; Julie Dimitry; William A. Frazier; Suzanne E. Lapi (Molecular Imaging)
CD47 functions as a marker of “self” by inhibiting phagocytosis of autologous cells. CD47 has been shown to be overexpressed by various tumor types as a means of escaping the antitumor immune response. The goal of this research was to investigate the utility of CD47 imaging using positron emission tomography (PET) in both human xenograft and murine allograft tumor models. Anti-CD47 antibodies were conjugated with p -isothiocyanatobenzyldesferrioxamine (Df-Bz-NCS) and labeled with 89 Zr. We employed xenograft and allograft small-animal models of cancer in biodistribution and PET imaging studies to investigate the specificity and PET imaging robustness of CD47. Ab-Df-Bz-NCS conjugates were labeled with 89 Zr with specific activity of 0.9 to 1.6 μCi/μg. Biodistribution studies in the xenograft and allograft model showed similar specific tumor uptake of the antihuman and antimouse CD47 antibodies. However, the tracer retention in the liver, spleen, and kidneys was significantly higher in the allograft-bearing animals, suggesting uptake mediated by the CD47 normally expressed throughout the reticular endothelial system. CD47, a marker of “self,” was evaluated as a diagnostic PET biomarker in xenograft and allograft cancer animal models. CD47 imaging is feasible, warranting further studies and immunoPET tracer development.